Efektivitas Aplikasi Sistem Informasi Pemerintah Daerah terhadap Kinerja Laporan Apbd Tahun Anggaran 2022 Di Bpkad Kota Cimahi - Amanda, Callula Ailsa; Sudrartono, Tiris (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to see the development of effectiveness of the Regional Government Information System (SIPD) application in BPKAD Cimahi City. This research uses descriptive qualitative research methods, with the existence of domestic regulation number 70 of 2019 which states that all regional devices are required to provide information related to regional financial information and other information through the SIPD application. The use of SIPD in BPKAD Cimahi City has various obstacles and benefits, one of the obstacles experienced is when preparing the 2022 APBD financial statements where there are several documents that cannot be inputted through the system making some SKPD have to input them manually and have to go to BPKAD, this causes ineffectiveness in preparing the 2022 APBD financial statements, and experiencing delays in document collection. BPKAD Cimahi City provides efforts to overcome this problem, namely by providing tutorials or procedures for inputting data properly and correctly and conducting training workshops on the use of SIPD.